Pandangan Mahasiswa Kost Desa Tuntungan Terhadap Mie Instan: Antara Ekonomi, Praktisitas, dan Kesadaran Kesehatan - Nazwa Panjaitan, Aulia; Hudzaifah, M. Harits; Aini Lubis, Nazwa Septi (PT. Alahyan Publisher Sukabumi, 2025)
Instant noodles are a food that is very popular with various levels of society. This food also has potential as a substitute for rice. Apart from having an economical price, instant noodles are also easy to find, because almost all minimarkets and supermarkets provide various brands of instant noodles, from well-known brands to new brands that continue to emerge. This research is a knowledge study to determine boarding house students' perceptions of instant noodles, both their knowledge and their behavior in consuming instant noodles. This research aims to analyze the views of boarding house students in Tuntungan Village regarding the consumption of instant noodles, by highlighting economic factors, practicality and health awareness. The research results revealed that the majority of students chose instant noodles for financial reasons of affordability and ease of serving, even though they understood the potential negative impact on health. This research concludes that although instant noodles are able to meet students' needs in terms of cost and practicality. The method we use is direct interviews, namely by asking several questions to students at the North Sumatara State Islamic University.